A practical and sustainable protocol for direct amidation of unactivated esters under transition-metal-free and solvent-free conditions. Issue 11 (12th May 2021) - Zhang, Rui; Yao, Wei-Zhong; Qian, Liang; Sang, Wei; Yuan, Ye; Du, Min-Chen; Cheng, Hua; Chen, Cheng; Qin, Xin
Abstract : An environmentally friendly and scalable protocol was developed for direct amidation of unactivated esters under transition-metal-free, solvent-free and chromatography-free conditions. Abstract : In this paper, a NaO t Bu-mediated synthesis approach was developed for direct amidation of unactivated esters with amines under transition-metal-free and solvent-free conditions, affording a series of amides in good to excellent yields at room temperature. In particular, an environmentally friendly and practical workup procedure, which circumvents the use of organic solvents and chromatography in most cases, was disclosed. Moreover, the gram-scale production of representative products 3a, 3w and 3au was efficiently realized by applying operationally simple, sustainable and practical procedures. Furthermore, this approach was also applicable to the synthesis of valuable molecules such as moclobemide (a powerful antidepressant), benodanil and fenfuram (two commercial agricultural fungicides). These results demonstrate that this protocol has the potential to streamline amide synthesis in industry. Meanwhile, quantitative green metrics of all the target products were evaluated, implying that the present protocol is advantageous over the reported ones in terms of environmental friendliness and sustainability. Finally, additional experiments and computational calculations were carried out to elucidate the mechanistic insight of this transformation, and one plausible mechanism was provided on the basis of these results and the related literature reports.